Synthesis of some new of thieno[2,3-b]pyridines, pyrazolo[1,5-a]pyrimidine, [1,2,4]triazolo[1,5-a]pyrimidine, pyrazolo[5,1-c]triazine and pyrimido[1,2-a]benzimidazole derivatives containing pyridine moiety - Mohamed, Mahmoud Abdallah; Abdelall, Eman Kamal Ahmad; Zaki, Yasser Hassan; Abdelhamid, Abdou Osman (European Journal of Chemistry, 2011)
pyrazolo[1,5-a]pyrimidine, [1,2,4]triazolo[1,5-a]pyrimidine and pyrimido[1,2-a] benzimidazole derivatives were synthesized by reaction of sodium salt of 3-hydroxy-(1-pyridin-2-yl)prop-2-en-1-one or sodium salt of 3-hydroxy-1-(pyridin-3-yl)prop-2-en-1-one with different heterocyclic amines in piperidenium acetate. Also, 3-amino-6-(2-pyridyl)thieno[2,3-b]pyridine derivatives were synthesized via reaction of pyridine-2-thione with various halogenated compounds. The structures of the newly synthesized compounds were confirmed by elemental analysis, spectral data, X-ray and alternative synthetic routes whenever possible.